Development of harmonised approaches for detecting and recording participant-reported anti-malarial drug safety data: The Delphi process - Mandimika, Nyaradzo (Department of Public Health and Family Medicine, 2018)
Eliciting adverse event (AE) and non-study medication reports from clinical research participants is integral for evaluating drug safety. However, using different methods to question participants yields inconsistent results, compromising the interpretation, comparison and pooling of data across studies. This is particularly important given the widespread use of antimalarials in vulnerable populations, and their increasing use in healthy but at-risk individuals as preventive treatment or to reduce malaria transmission. Experienced, qualified antimalarial drug clinical researchers were invited to participate in a Delphi process, to facilitate consensus on what panellists consider to be optimal (relevant, important and feasible) methods, tools, and approaches for detecting participant-reported AE and non-study medication data in uncomplicated malaria treatment studies. This Delphi built on a previous survey conducted among malaria clinical researchers about different elicitation methods they used. The findings thereof, and a summary of relevant literature, were presented to Delphi panellists in round one after which they were asked to suggest further questioning methods or approaches that they considered as important and feasible for asking participants (or their caregivers) about their health to collect adverse events, and use of non-study medications to collect previous or concomitant medication data. In round two, the panellists were presented with the collated suggestions from round one to rate each type of question in terms of its relevance, importance and feasibility. Here, panellists would rate methods or approaches as either optimal or not optimal for inclusion in a 'menu' of harmonized or standard types of core questions to be used in a variety of uncomplicated antimalarial treatment studies. In round three, panellists were presented with a summary of items which had achieved consensus in round two and, for items that had not achieved consensus they were asked whether or not they wished to change their response in view of the group's overall response. Of the 72 invited, 25; 16 and 10 panellists responded to the first, second and third rounds of the Delphi process respectively. Overall, 68% of all questioning items presented for rating achieved consensus. When asking general questions about health, panellists agreed to include a question/concept about any change in health, taking care to ensure that such questions/concepts do not imply causality. Eighty-nine percent (39/44) of structured items about specific signs and symptoms, were rated as optimal. For non-study medications, a general question and most structured questioning items were considered an optimal approach. The use of mobile phones, patient diaries, rating scales as well as openly engaging with participants to discuss concerns were also considered optimal complementary data-elicitation tools. This study succeeded in reaching consensus within a section of the antimalarial drug clinical research community about using a general question concept, and some structured questions for eliciting data about AEs and non-study medication reports. The findings suggest that one method of questioning may not be superior to another, or sufficient to fulfil its purpose on its own and that the use of a combination of methods may be optimal. As malaria clinical research is often conducted in children (and other vulnerable groups), this becomes an important consideration in the design of appropriate elicitation methods cognisant of any particular factors that may impede accurate reporting in these groups. The concepts and items found in this Delphi survey to be relevant, important and feasible should be further investigated for potential inclusion in a harmonised approach to collect participant-elicited antimalarial drug safety data. This, in turn, should improve understanding of antimalarial drug safety.